PERAN STRATEGIS ORGANISASI ZAKAT DALAM MENGUATKAN ZAKAT DI DUNIA - Hafidhuddin, Didin (Al-Infaq: Jurnal Ekonomi Islam, 2011)
One of the potentials which are still not utilized by the ummah is zakat fund. In Indonesia, this potential reaches 2 percent of GDP, which is not less than Rp 100 trillion per annum. As could be witnessed in the history, the use of zakat was able to alleviate poverty, especially during the glorious era of Caliph Umar bin Abdul Aziz. This paper attempts to discuss the strategies needed in order to realize the country's zakat potential. In addition, strengthening global zakat cooperation and network is highly needed as an effective way to overcome poverty which still exists in the Muslim world.